Dual Function of a in vivo Albumin-Labeling Tracer for Assessment of Blood Perfusion and Vascular Permeability in Peripheral Arterial Disease by PET - Sun, Zhongchan; Tong, Guang; Liu, Yuanhui; Fan, Hualin; He, Weibin; Wang, Bo; Xia, Shuang; He, Pengcheng (Frontiers in Cardiovascular Medicine, 2022)
Background: Peripheral arterial disease (PAD) leads to tissue ischemia in the extremities. Enhanced vascular permeability plays a critical role in targeted delivery of drugs for effective therapeutic angiogenesis and resultant blood perfusion recovery. However, optimal tracers for evaluating this process in PAD patients are lacking. At this time, we employed a novel in vivo albumin-labeling tracer of dual function, termed as 18F-NEB, to assess blood perfusion as well as vascular permeability by positron emission tomography (PET). Methods and Results: After successful establishment of mouse hindlimb ischemia (HI) model, static PET imaging was performed 15 minutes and 2 hours post injection (p.i.) of 18F-NEB at 1, 3, 5, 7, 10 and 14 days post-surgery respectively. Gradual recovery of blood supply was detected by PET scan 15 minutes p.i. and collaborated by serial Laser Doppler. In addition, the highest vascular permeability observed by high local uptake of 18F-NEB at 2 hours p.i. was consistent with histological examinations. Furthermore, we quantitatively evaluated the effect of vascular endothelial growth factor (VEGF) stimulus on vascular permeability and blood perfusion by PET scan using 18F-NEB probe in HI model, which were also confirmed by immunohistological results. Conclusion: The application of 18F-NEB probe alone by PET can successfully achieve dual imaging of blood perfusion as well as vascular permeability at different time points p.i. and monitor their responses to therapy in PAD model. The simple labeling approach and multipurpose feature suggest the great promise of using this imaging probe in theranostic applications for treating ischemic disease.